Neuropsychological feedback services improve quality of life and social adjustment. Issue 3 (3rd April 2018) - Rosado, Dana L.; Buehler, Susan; Botbol-Berman, Emilie; Feigon, Maia; León, Adeline; Luu, Hien; Carrión, Carmen; Gonzalez, Mitzi; Rao, Julia; Greif, Taylor; Seidenberg, Michael; Pliskin, Neil H.
Abstract: Objective: In more recent years, studies have begun to examine levels of satisfaction of individuals or family members of individuals who undergo neuropsychological evaluation. However, to date there have been only a handful of formal studies that have specifically examined the role and contribution of neuropsychological assessment in patient care and management. This study sought to examine one specific component of neuropsychological assessment, namely the impact of patient feedback regarding neuropsychological testing on patient outcome.Method: Participants included 218 patients who were recruited from a neuropsychological outpatient clinic at a Midwest academic medical center. This study examined potential differences between outcome measures for patients who attended feedback sessions versus those who did not receive direct feedback.Results: Results indicated that compared with the No Feedback group, the Feedback group reported greater improvement in quality of life, increased understanding of their condition, and an increased ability to cope with their condition at follow-up. There were no significant demographic differences between the Feedback and No Feedback group.Conclusions: These findings suggest that there is benefit for the individuals who chose to engage in feedback sessions. Feedback sessions can be utilized to assist with integral decision-making processes and assisting in treatment planning among other areas. It also allows time for patients and family members to discuss their concerns regarding important test findings and recommendations. Given the current climate of value-based services and clinical outcomes, the findings from this study lend support to the utility of neuropsychological assessments and, in particular, the role of feedback within neuropsychological evaluations.